A translation enhancer element from black beetle virus engages yeast eIF4G1 to drive cap-independent translation initiation - Brandon M. Trainor (Nature Portfolio, 2021)
Abstract Cap-independent translation initiation plays crucial roles in fine-tuning gene expression under global translation shutdown conditions. Translation of uncapped or de-capped transcripts can be stimulated by Cap-independent translation enhancer (CITE) elements, but the mechanisms of CITE-mediated translation initiation remain understudied. Here, we characterized a short 5ʹ-UTR RNA sequence from black beetle virus, BBV-seq. Mutational analysis indicates that the entire BBV-seq is required for efficient translation initiation, but this sequence does not operate as an IRES-type module. In yeast cell-free translation extracts, BBV-seq promoted efficient initiation on cap-free mRNA using a scanning mechanism. Moreover, BBV-seq can increase translation efficiency resulting from conventional cap-dependent translation initiation. Using genetic approaches, we found that BBV-seq exploits RNA-binding properties of eIF4G1 to promote initiation. Thus, BBV-seq constitutes a previously uncharacterized short, linear CITE that influences eIF4G1 to initiate 5′ end-dependent, cap-independent translation. These findings bring new insights into CITE-mediated translational control of gene expression.